Pelatihan Mendesain Pembelajaran Berbasis Multimedia di Kalangan Guru MIN 11 Aceh Tenggara - Harpan Reski Mulia (Jurnal Ilmiah Pangabdhi, 2020)
Teachers should be able to respond to technological developments, especially about technologies that support the learning process, such as making learning media by utilizing technology. Microsoft Office PowerPoint, is one of the media that can be used in designing more interesting learning. Because, with the help of Microsoft Office PowerPoint, the teacher can design learning that combines several media, such as audio, images, text and so on or called multimedia. To overcome the inability of teachers to design multimedia-based learning, training needs to be held. This paper is an exploration of the training activities conducted by the author of teachers in MIN 11 Aceh Tenggara. The results of the activity showed that, every teacher in MIN 11 Aceh Tenggara already had a laptop as a medium for making PowerPoint, the obstacle faced was how to operate it that could not. Then, after doing the training the teacher felt that the use of PowerPoint was very helpful in making learning interesting and fun, and students were also more enthusiastic and motivated in participating in the learning, because students felt that they seemed to be directly in the events set forth in Power point.